FORMATION OF INDIVIDUAL READINESS FOR INNOVATIVE ACTIVITIES IN WORLD EDUCATIONAL AND SCIENTIFIC INSTITUTIONS: Kurbanov Ikhtiyor Khikmatovich - Bukhara, Uzbekistan, postal code 200100 Bukhara State Medical Institute named after Abu Ali ibn Sina, Uzbekistan, Kurbanov Ikhtiyor Khikmatovich (Лучшие интеллектуальные исследования, 2024)
This article describes the methods, means and main tasks of forming the psychological readiness of a person for innovative activity, as well as ways to prepare future professors and teachers for innovative activity as one of the areas of training specialists for professional activity. The essence and content of the psychological readiness of the individual (and future specialists) of the healthcare sector for innovative activity and the development on this basis of a model of its formation in the conditions of higher professional education are revealed. The subject of the study is the process of formation of psychological readiness for innovation among future healthcare professionals in the process of their studies at the university.